2012
DOI: 10.4103/0976-7800.104467
|View full text |Cite
|
Sign up to set email alerts
|

Health issues of menopausal women in North India

Abstract: Objective:To evaluate the health status, age of menopause, and its symptomatology amongst Himachali middle-aged women.Materials and Methods:A community based cross-sectional study was done from Jul 07 to Jan 08. A structured questionnaire was given to 100 menopausal women from general community of Himachal Pradesh in Shimla.Results:Mean age of menopause was 44.54 years. Main symptoms associated with menopause were reported as fatigue (62%), hot flashes (56%), Cold sweats (52%), and backaches (51%). Other ailme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
73
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 18 publications
2
73
4
1
Order By: Relevance
“…Mahajan N, et al in Shimla, Himachal Pradesh in their study reported that the prevalence of hypertension was 23% which is comparable to the present study. 9 In the present study increased sugar level was found in 23% of rural women and 29.5% of urban women. Nusrat N, et al in Hyderabad Sindh, Pakistan reported that the prevalence of diabetes was 24.9% which is comparable to the findings of rural area in the present study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Mahajan N, et al in Shimla, Himachal Pradesh in their study reported that the prevalence of hypertension was 23% which is comparable to the present study. 9 In the present study increased sugar level was found in 23% of rural women and 29.5% of urban women. Nusrat N, et al in Hyderabad Sindh, Pakistan reported that the prevalence of diabetes was 24.9% which is comparable to the findings of rural area in the present study.…”
Section: Discussionmentioning
confidence: 67%
“…8 The relationship of menopausal age with the risk factors for such medical conditions makes age at menopause an important epidemiological issue. 9 Among the post-menopausal symptoms, the most frequently reported ones were vasomotor symptoms (60.9%), followed by sleep related symptoms (40.1%) and anxiety (35.4%). 10 The epithelium of the bladder and urethra also undergo atrophic changes.…”
mentioning
confidence: 99%
“…Dysfunctional uterine bleeding is among the most common causes of admissions to the Gynecology Outpatient Clinic and observed in approximately 20% of the women in reproductive age [8]. Causes such as endometrial polyp, endometrial hyperplasia, myoma uteri, and endometrial cancer (EC) should certainly be excluded beside systemic, iatrogenic, and hormonal causes in patients who present with dysfunctional uterine bleeding [8].…”
Section: Discussionmentioning
confidence: 99%
“…Causes such as endometrial polyp, endometrial hyperplasia, myoma uteri, and endometrial cancer (EC) should certainly be excluded beside systemic, iatrogenic, and hormonal causes in patients who present with dysfunctional uterine bleeding [8]. The main goal of endometrial sampling is to exclude EC [9], and endometrial sampling performed with the aim of controlling bleeding is controversial [10].…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for more than 70% of all gynaecological consultations in the peri-and postmenopausal age group. 4 In the present study, 180 numbers of perimenopausal women presenting with abnormal uterine bleeding were analysed. Most number of patients (63.89%) was 40-45 years of age group.…”
Section: Discussionmentioning
confidence: 99%